THEOLOGICAL AND SPIRITUAL MEANING IN THE REPETITION OF THE WORD ALLAH IN SURAH AL-MUJADILAH - Anwar; Dian Erwanto (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
Surah Al-Mujadilah has a unique linguistic feature in the Quran, namely the consistent mention of the word Allah in every verse, a total of 40 times in 22 verses. This phenomenon invites attention for in-depth study, especially in its theological and spiritual aspects. This research uses a qualitative method with a thematic (maudhū‘ī) approach to Surah Al-Mujadilah, and the analysis is based on the classical interpretation of Ibn Jarir At-Thabari. The research findings indicate that the repetition of the word "Allah" in this surah carries profound theological meaning, namely as an affirmation of Allah's presence and supervision in every aspect of human life, especially in social and legal contexts. Spiritually, this repetition shapes the spiritual awareness of its readers, fostering an attitude of muraqabah (spiritual contemplation), taqwa (piety), and submission to divine laws in family, community, and political life. Thus, it can be concluded that the repetition of the word Allah in Surah Al-Mujadilah is not merely a rhetorical element, but rather a divine strategy to instill the concept of monotheism and build a strong Islamic spirituality amidst the dynamics of human life.